2010
DOI: 10.1111/j.1542-474x.2010.00376.x
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of T‐Wave Alternans in Sudden Death Risk Stratification and Guiding Medical Therapy

Abstract: Visible T-wave alternans (TWA), a beat-to-beat alternation in the morphology and amplitude of the ST segment or T wave, has been observed for over a century to occur in association with life-threatening arrhythmias in patients with acute coronary syndrome, heart failure, and cardiac channelopathies. This compelling linkage prompted development of quantitative techniques leading to FDA-cleared commercial methodologies for measuring nonvisible levels of TWA in the frequency and time domains. The first aim of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 77 publications
1
25
0
2
Order By: Relevance
“…TWA following sGTCS seems to be an independent marker, as it did not correlate with HR and returned to baseline after 15 min, in contrast to the impaired HR recovery, which lasted for at least 30 min after seizure cessation. Experimental studies have demonstrated that HR is only one determinant of TWA, as autonomic neurotransmitters and changes in myocardial substrate can provoke elevated levels of TWA during fixed rate pacing (Nieminen & Verrier, 2010). Furthermore, TWA was not different at both baselines at 4:00 a.m. and 8:00 a.m. as compared to otherwise healthy patients with NREM parasomnia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TWA following sGTCS seems to be an independent marker, as it did not correlate with HR and returned to baseline after 15 min, in contrast to the impaired HR recovery, which lasted for at least 30 min after seizure cessation. Experimental studies have demonstrated that HR is only one determinant of TWA, as autonomic neurotransmitters and changes in myocardial substrate can provoke elevated levels of TWA during fixed rate pacing (Nieminen & Verrier, 2010). Furthermore, TWA was not different at both baselines at 4:00 a.m. and 8:00 a.m. as compared to otherwise healthy patients with NREM parasomnia.…”
Section: Discussionmentioning
confidence: 99%
“…Impaired cardiac recovery as assessed by persistent elevations of HR after exercise or decreased HRV are long‐established electrocardiographic predictors of arrhythmic death (McLaughlin & Zimetbaum, 2006). During the past decade T‐wave alternans (TWA) has been identified as a novel independent predictor of risk of sudden cardiac death and cardiovascular mortality (Hering, 1909; Rosenbaum et al., 1994; Nieminen & Verrier, 2010). TWA is a beat‐to‐beat alternation in morphology and amplitude of the ST segment or T wave that reflects temporal‐spatial heterogeneity of repolarization (Nearing & Verrier, 2003).…”
mentioning
confidence: 99%
“…This method has been described in detail in the original report. 11,19 Briefly, the modified moving average algorithm continuously streams odd and even beats into separate bins and creates median complexes at any point within the JT segment and it is regarded as the TWA value, which is updated every 15 seconds. The moving average algorithm allows control of the influence of new incoming beats on the median complexes with an adjustable update factor, which was 1/8 in this analysis.…”
Section: Twa and Qt Dispersion Measurementmentioning
confidence: 99%
“…Experimental [2,3] and clinical [4] studies indicate that TWA appears in cases of temporal-spatial heterogeneity of ventricular repolarization, which is a critical factor in arrhythmogenesis arising in different cardiac pathologies. The phenomena can establish the preconditions for conduction block, reentry, and life-threatening arrhythmias what may cause sudden cardiac death [5,6].…”
Section: Introductionmentioning
confidence: 99%